A wireless self-powered sensor network based on dual-model convolutional neural network algorithm for tennis sports - Li, Y.; Wu, L. (IEEE Sensors Journal, 2023)
More and more scholars turn their attention to the use of digital and systematic management methods to further improve the safety and effectiveness of tennis. At present, most of these systems are based on video monitoring technology, and their actual operation process is limited by the deployment environment, and the cost is very high. In order to obtain the track of tennis players, this paper uses the sensor array in the intelligent insole to collect the original data. A Dual-model Convolutional Neural Network (DMCNN) structure is designed to further improve the computational efficiency and accuracy of tennis players` gait recognition. Combined with quaternion and complementary filtering algorithm, the rotation matrix is established to convert the data in the sensor coordinate system to the reference coordinate system. Use multiple sensors in the smart insole to collect linear and curve track data from tennis players. After the unit conversion and normalization of the original data, the acceleration and angular velocity data in the sensor coordinate system are converted to the reference coordinate system by using quaternions to represent the rotation matrix and using complementary filtering algorithm to update the quaternions. The experimental results show that the displacement error of the scheme is small and the performance is good when the track tracking of tennis players is realized. The error between the estimated distance and the actual distance is within 6%, which proves the accuracy of the linear trajectory experiment.